The Chinese Influence on the Various Architectural Elements in the Palembang Limas Traditional House - Isti, Adelina Ratika; Idham, Noor Cholis; Sugini, Sugini (Green Publisher Indonesia, 2024)
This study aims to inventory the influence of Chinese culture on the forms, elements, and ornaments of the Limas Traditional House in Palembang. The method that used in this study was through observing 4 original buildings, namely, the house of the Cek Mas family, the SMB Museum, the residence of the Mr. H. Rozak, and the residenceof Mr. Aziz family. The study was carried out through field observations and also analyzing the architectural elements contained in the 4 original houses in the city. The results show that the most dominant Chinese influence in the house is the use of wood material for almost all parts of the house ranging from walls, floors, ornaments, to the construction of the House. The investment in the House can serve as a valuable learning resource for future generations, considering its endangered condition.